1983
DOI: 10.1139/x83-158
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of sequential sampling plans based on Wald's sequential probability ratio test

Abstract: Monte Carlo operating characteristic (OC) and average sample number (ASN) functions were compared with Wald's OC and ASN equations for sequential sampling plans based on Wald's sequential probability ratio test (SPRT) using the binomial, negative binomial, normal, and Poisson distributions. This comparison showed that the errors inherent in Wald's equations as a result of "overshooting" the decision boundaries of the SPRT can be large. Relative errors increased for the OC and ASN equations as the difference be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…density has exceeded a critical threshold associated with epidemic transmission. The statistical properties, assumptions, and errors associated with this method have been well documented (Wald 1947, Fowler 1983, Fowler and Lynch 1987b and it has been applied previously to mosquito control (Mackey and Hoy 1978).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…density has exceeded a critical threshold associated with epidemic transmission. The statistical properties, assumptions, and errors associated with this method have been well documented (Wald 1947, Fowler 1983, Fowler and Lynch 1987b and it has been applied previously to mosquito control (Mackey and Hoy 1978).…”
Section: Methodsmentioning
confidence: 99%
“…Intermediate between these two levels, larger sample sizes are required to reach a conclusion. It should be noted that the functions for the operating characteristic curve and expected average number of houses are only approximate because of overshooting the threshold when decisions are made (Fowler 1983). The result of overshooting is that actual values for ␣ and ␤ are less than those chosen to construct the sampling plan, whereas the number of houses needed in the Þeld to reach a terminating decision may be more than that indicated by WaldÕs average sample number function.…”
Section: Figmentioning
confidence: 99%
“…Alternatively, once a decision has been made using a division of multiple categories, and sample examination ceased, iterations could be undertaken using already collected count data as in the present study to achieve a modal abundance rank (i.e., in a sense, a simplified form of bootstrapping). Similarly, Fowler (1983) used Monte Carlo simulations to reduce the number of samples needed in field surveys.…”
Section: Sequential Samplingmentioning
confidence: 99%
“…For example, the Statistical Research Group (1946) reported that as little as 400Jo of the samples normally needed in fixed sample size inventories were needed for a sequential sampling inventory to make an appropriate decision. Fowler (1988) similarly stated that only 40-60 per cent as many observations are required in sequential sampling as in an equally reliable fixed sample size procedure. Sequential sampling has been primarily used in forestry for ·deciding whether insect infestations have reached sufficient intensity to justify control (e.g.…”
Section: Introductionmentioning
confidence: 99%